Chemical reprogramming enhances homology-directed genome editing in zebrafish embryos - Aksoy, Yagiz A. (Commun Biol, 2019)
Precise genome editing is limited by the inefficiency of homology-directed repair (HDR) compared to the non-homologous end-joining (NHEJ) of double strand breaks (DSBs). The CRISPR (clustered regularly interspaced short palindromic repeat)/Cas9 system generates precise, locus-specific DSBs that can serve as substrates for HDR. We developed an in vivo visual reporter assay to quantify HDR-mediated events at single-cell resolution in zebrafish and used this system to identify small-molecule modulators that shift the DNA repair equilibrium in favor of HDR. By further optimizing the reaction environment and repair template, we achieved dramatic enhancement of HDR-mediated repair efficiency in zebrafish. Accordingly, under optimized conditions, inhibition of NHEJ with NU7441 enhanced HDR-mediated repair up to 13.4-fold. Importantly, we demonstrate that the increase in somatic HDR events correlates directly with germline transmission, permitting the efficient recovery of large seamlessly integrated DNA fragments in zebrafish.